"In Turcia mors cum vita commixta est": ambigviteti i ambivalencije "otomanističkog" diskursa Bartola Đurđevića - Blažević, Zrinka (2004)
After having escaped from thirty-years long Ottoman captivity Bartol Djurdjevic (cca. 1506-1566) capitalised his knowledge about the cultural Other writing few booklets on ritus et mores Turcarum which went through countless printings and translations all over Europe for more than two centuries. He has been soon promoted into one of the most influential creators of early modern "Ottoman" discourse, a rich inventory of cultural images and stereotypes about simultaneously intimidating and alluring world-life of Muslims. Although constutive propositon of Djurdjevic's discourse is incommesurability and clear distinction between Christian "we" and Muslim "them", both liminality of author's cultural experience and pragmatics of text itself make these symbolic boundaries vague and blurred. In my analysis of Djurdjevic's text I will focus on mechanism of cultural translation and its influence on processes of discursive de/stabilisations as well as textual inscriptions of Other. In contrast to traditional orientalist approach, my atempt will be showing "Ottoman" discourse as a multidimensional and heterogeneous textual space able to argue and justify different and even contradictory interpretations and thus verify various political usages.